Rethinking ethics through hypertext - Garcia, Dominic (Emerald Publishing Limited, 2019)
This book considers how social justice and authentic freedom of speech could be better tackled through hypertextual writing. Unilinear writing produces an artificial understanding of justice, freedom of speech and hermeneutics. In contrast, hypertextual writing promises an optimistic future which involves less judgment, more empathy and the embracing of difference, so vital in our post-truth culture. The author argues that hypertextual writing is set to have a marked impact on fields like jurisprudence, social sciences and education. Rethinking Ethics Through Hypertext reconciles traditional theories of ethics by re-framing them through hypertextual techniques, bringing together contrasting and contradictory ethical views. It presents compelling insights for scholars of moral philosophy, social justice, hermeneutics and education.